2010
DOI: 10.1590/s0004-27302010000300009
|View full text |Cite
|
Sign up to set email alerts
|

Evolução e classificação do peso corporal em relação aos resultados da cirurgia bariátrica: derivação gástrica em Y de Roux

Abstract: Objetivo: Avaliar a evolução e a classificação do peso corporal em relação aos resultados da cirurgia bariátrica em mulheres submetidas ao procedimento cirúrgico há mais de dois anos. Sujeitos e método: Foram avaliadas 141 mulheres submetidas à derivação gástrica em Y de Roux (DGYR) com anel de contenção. As participantes foram divididas de acordo com o tempo de pós-operatório e conforme o percentual da perda do excesso de peso (%PEP): < 50; 50 ┤ 75; e, ≥ 75. Resultados: As mulheres do grupo com %PEP ≤ 50 (15,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
12

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 32 publications
2
18
0
12
Order By: Relevance
“…According to the study's authors, weight loss is one of the primary parameters for demonstrating the efficacy of bariatric surgery, since it is after weight loss has taken place that patient health improves, as a result of lower nutritional intake and reduced gastric volume, which provoke significant improvements or even remission of the comorbidities caused by obesity, such as arterial hypertension, diabetes, cardiac problems, and others. 18 With regard to metabolic profiles, our results showed that levels of LDL, total cholesterol, and triglycerides all reduced gradually, while HDL levels increased, which is in agreement with a study that followed 130 patients from before surgery up to 12 months after it had been performed. 19 A recent meta-analysis encompassing 178 studies showed that 1 year after the surgical procedure there had been significant reductions in total cholesterol, LDL cholesterol, and triglycerides, while HDL cholesterol had increased.…”
Section: Discussionsupporting
confidence: 91%
“…According to the study's authors, weight loss is one of the primary parameters for demonstrating the efficacy of bariatric surgery, since it is after weight loss has taken place that patient health improves, as a result of lower nutritional intake and reduced gastric volume, which provoke significant improvements or even remission of the comorbidities caused by obesity, such as arterial hypertension, diabetes, cardiac problems, and others. 18 With regard to metabolic profiles, our results showed that levels of LDL, total cholesterol, and triglycerides all reduced gradually, while HDL levels increased, which is in agreement with a study that followed 130 patients from before surgery up to 12 months after it had been performed. 19 A recent meta-analysis encompassing 178 studies showed that 1 year after the surgical procedure there had been significant reductions in total cholesterol, LDL cholesterol, and triglycerides, while HDL cholesterol had increased.…”
Section: Discussionsupporting
confidence: 91%
“…A restrição no consumo alimentar provocada pela cirurgia bariátrica desencadeia grande perda de peso, considerada como um dos principais resultados para um bom desfecho, levando à melhora das condições clínicas do indivíduo [17]. A PEP é expressiva no primeiro mês pós-cirúrgico e há tendência de se acentuar até o sexto mês, quando começa a estabilizar, fato esse concretizado entre o 12º e 18º mês de pós-operatório [26].…”
Section: Discussionunclassified
“…A PEP é expressiva no primeiro mês pós-cirúrgico e há tendência de se acentuar até o sexto mês, quando começa a estabilizar, fato esse concretizado entre o 12º e 18º mês de pós-operatório [26]. É consenso na literatura que o tratamento cirúrgico da obesidade obtém sucesso quando o %PEP é de no mínimo 50%, com manutenção por um longo período [17]. Neste estudo, verificou-se um %PEP médio bem acima desse valor.…”
Section: Discussionunclassified
See 2 more Smart Citations